Using nurses for preventive activities with computer assisted follow up: a randomised controlled trial. Issue 6671 (18th February 1989) - Robson, J.; Boomla, K.; Fitzpatrick, S.; Jewell, A. J.; Taylor, J.; Self, J.; Colyer, M.
Abstract : OBJECTIVE--To assess whether an organised programme of prevention including the use of a health promotion nurse noticeably improved recording and follow up of cardiovascular risk factors and cervical smears in a general practice that had access to computerised cell and recall. DESIGN--Randomised controlled trial. SETTING--General practice in inner London. PATIENTS--All 3206 men and women aged 30-64 registered with the practice. INTERVENTION--The intervention group had their risk factors ascertained and followed up by the health promotion nurse and the general practitioner, whereas those in the control group were managed by the general practitioner alone. END POINT--Recording and follow up of blood pressure and cervical smears after three years. Recording of smoking, family history of ischaemic heart disease, and serum cholesterol concentrations were also examined. MEASUREMENTS and MAIN RESULTS--When the trial was stopped after two years the measurements of blood pressure in the preceding five years were 93% (1511/1620) v 73% (1160/1586) (95% confidence interval for difference 17.5 to 22.7%) for intervention and control groups respectively. For patients with hypertension the figures were 97% (104/107) v 69% (80/116) (18.2 to 38.2%). For women the proportion who had had a cervical smear in the preceding three years were 76% (606/799) v 49% (392/806) (22.5 to 31.9%). Recording of smoking, family history of ischaemic heart disease, and serum cholesterol concentrations was also higher in the intervention group compared with the control group. CONCLUSION--An organised programme, which includes a nurse with specific responsibility for adult prevention, is likely to make an important contribution to recording of risk factors and follow up of those patients with known risks.